Patients' experiences of care provided by emergency care practitioners and traditional ambulance practitioners: a survey from the London Ambulance Service. Issue 11 (20th October 2006) - Halter, M; Marlow, T; Tye, C; Ellison, G T H
Abstract : Patients' experiences after receiving care from emergency care practitioners (ECPs) were compared with those after receiving care from traditional ambulance practitioners using a postal questionnaire distributed to 1658 patients in London; 888 responses were received. The responses of patients receiving care from both groups were similar and largely positive. But in two areas ("thoroughness of assessment" and "explaining what would happen next"), the care provided by ECPs was experienced as considerably better. These differences were partly explained by considerably fewer patients from ECPs being conveyed to the emergency department, suggesting that empowering ECPs to explore and explain alternatives to the emergency department improves patient satisfaction.